7A.06: MATERNAL OBESITY AND THE DEVELOPMENTAL PROGRAMMING OF HYPERTENSION. (June 2015) - Lim, J.; Burke, S.; Head, G. A.
Abstract : Objective: The prevalence of obesity in women among child baring age is increasing and this has been parallel to the increase in obesity in general population around the world. We investigated the trans-generational 'programming' of leptin signalling in the central nervous system (CNS) to increase blood pressure (BP), heart rate (HR) and renal sympathetic nerve activity (RSNA) following a high fat diet (HFD)feeding in mothers. Design and method: Female New Zealand White rabbits were fed a high fat (13%) diet (mHFD) or a control diet (mCD) prior mating and during pregnancy. Kittens from mCD rabbits were subdivided and fed HFD for 10days (mCD10dHFD) at 15 weeks of age. All rabbits received an intracerebroventricular (ICV) catheter into the lateral ventricle and a recording electrode on the left renal nerve. Experiments were conducted in conscious rabbits and BP, HR and RSNA was measured. Rabbits received an increasing doses of ICV Melanocortin receptor antagonist (SHU9119), alpha-Melanocortin stimulating hormone (alpha-MSH) and a single dose of Leptin antagonist. Results: ICV SHU9119 reduced BP (-5.8 ± 0.7mmHg and -4.1 ± 0.9mmHg) and RSNA (-2.4 ± 0.3 nu and -0.7 ± 0.3 nu) in mHFD and mCD10dHFD rabbits (P < 0.001). Leptin antagonist reduced BP and RSNA only in mHFD rabbits (-2.1 ± 0.5mmHg and -2.7nu, respectively). alpha-MSH injection increased BP, HR and RSNA in both mHFD and mNFD10dHFD rabbits (P < 0.05). Total % fat was increased (50%) in all rabbits that had HFD. Conclusions: Obesity during pregnancy 'programs' leptin signalling pathway in the CNS of the offspring during development. Leptin via activation of melanocirtin pathway plays a key role in the CNS contributing to the pressor and tachycardic effects as well as renal sympathetic nerve activity in the pathophysiology of obesity.